Chemical Chaperones to Inhibit Endoplasmic Reticulum Stress: Implications in Diseases - Jeon JH; Im S; Kim HS; Lee D; Jeong K; Ku JM; Nam TG (Dove Medical Press, 2022)
Jae-Ho Jeon,1,* Somyoung Im,1,* Hyo Shin Kim,1 Dongyun Lee,1 Kwiwan Jeong,2 Jin-Mo Ku,2 Tae-Gyu Nam1 1Department of Pharmacy and Institute of Pharmaceutical Science and Technology, Hanyang University ERICA campus, Ansan, Gyeonggi-do, 15588, Republic of Korea; 2Gyeonggi Bio-Center, Gyeonggido Business and Science Accelerator, Suwon, Gyeonggi-do, 16229, Republic of Korea*These authors contributed equally to this workCorrespondence: Tae-Gyu Nam, Tel +82-31-400-5807, Fax +82-31-400-5958, Email tnam@hanyang.ac.krAbstract: The endoplasmic reticulum (ER) is responsible for structural transformation or folding of de novo proteins for transport to the Golgi. When the folding capacity of the ER is exceeded or excessive accumulation of misfolded proteins occurs, the ER enters a stressed condition (ER stress) and unfolded protein responses (UPR) are triggered in order to rescue cells from the stress. Recovery of ER proceeds toward either survival or cell apoptosis. ER stress is implicated in many pathologies, such as diabetes, cardiovascular diseases, inflammatory diseases, neurodegeneration, and lysosomal storage diseases. As a survival or adaptation mechanism, chaperone molecules are upregulated to manage ER stress. Chemical versions of chaperone have been developed in search of drug candidates for ER stress-related diseases. In this review, synthetic or semi-synthetic chemical chaperones are categorized according to potential therapeutic area and listed along with their chemical structure and activity. Although only a few chemical chaperones have been approved as pharmaceutical drugs, a dramatic increase in literatures over the recent decades indicates enormous amount of efforts paid by many researchers. The efforts warrant clearer understanding of ER stress and the related diseases and consequently will offer a promising drug discovery platform with chaperone activity.Keywords: endoplasmic reticulum stress, unfolded protein response, chemical chaperone, drug discovery, diabetes, cardiovascular disease, neurodegeneration, lysosomal storage disease